Hepatic Epithelioid Hemangioendothelioma and Adult Liver Transplantation: Proposal for a Prognostic Score Based on the Analysis of the ELTR-ELITA Registry. Issue 3 (March 2017) - Lai, Quirino; Feys, Estelle; Karam, Vincent; Adam, Rene; Klempnauer, Jurgen; Oliverius, Martin; Mazzaferro, Vincenzo; Pascher, Andreas; Remiszewski, Piotr; Isoniemi, Helena; Pirenne, Jacques; Foss, Aksel; et al.
Abstract : Background: Hepatic epithelioid hemangioendothelioma (HEHE) is a rare vascular tumor which has an intermediate aggressive behavior. Although the value of liver transplantation (LT) is well established, its place in the management of HEHE is still unclear. The aim of this study is to confirm, based on a very large patient cohort, the value of LT in the management of HEHE and to identify risk factors for post-LT recurrence. Methods: The outcome of 149 transplant recipients with HEHE recorded in the European Liver Transplant Registry during the period November 1984 to May 2014 was analyzed. Median post-LT follow-up was 7.6 years (interquartile range, 2.8-14.4). Results: Cox regression analysis showed that macrovascular invasion (hazard ratio [HR], 4.8; P < 0.001), pre-LT waiting time of 120 days or less (HR, 2.6; P = 0.01) and hilar lymph node invasion (HR = 2.2; P = 0.03), but not pre-LT extrahepatic disease, were significant risk factors for recurrence. These findings, which were also confirmed in a propensity score analysis, allowed the development of a HEHE-LT score enabling stratification of patients in relation to their risk of tumor recurrence. Patients with a score of 2 or less had a much better 5-year disease-free survival compared to those having a score of 6 or higher (93.9% vs 38.5%; P < 0.001). Conclusions: The analysis of this (largest in the world) HEHE adult liver recipient cohort clearly confirms the value of LT in the treatment of this rare disorder and also permits identification of patients at risk of posttransplant recurrence. Posttransplant follow-up should take the HEHE-LT score into account. Extrahepatic disease localization is reconfirmed not to be a contraindication for LT. Abstract : This study updates the ELTR experience with HEHE. The findings from this larger cohort substantiate the role of OLT in HEHE and identify rapid transplantation and microvascular invasion as predictors of poor outcomes while extrahepatic disease is not. The authors also affirm the overall improvement in outcomes that seem primarily reflective of improved patient selection.